El corazón helado de Almudena Grandes: el miedo y la memoria frente al pasado reciente - Crespo, Marcela Gladys (2013)
Has been emerging in Spanish literature of the last decades a series of stories that try, with varying degrees of zeal revisionist reinterpretation of recent historical events, especially those related to the Civil War, the postwar crisis and Exile. This is demonstrated by novels like La voz dormida by Dulce Chacón (2002), La desbandá by Luis Melero (2005), Los años del miedo by Juan Eslava Galán (2008) and, among other representatives and getting creditor of two major awards: the Prize Book of the year 2007, awarded by the Guild of Booksellers in Madrid and José Manuel Lara Award 2008, Almudena Grandes begins with his novel El corazón helado a dangerous and conflicted way that historical memory retrieval. This short exercise to analyze the identity conflict of the children of Spanish Republican exile in Grandes’ novel.